Effect of Balance Excercise on Reducing the Falling Risk in Elderly - Arip, Moh.; Fathoni, Akhmad; Sulaeman, Ridawati (International Journal of Psychosocial Rehabilitation, 2020)
The elderly is a group of people who lived a processes of life that has a longer time to adapt to the environtment so it is potentially a declining in all the body’s ability. This declining led to the balance reduction, including the postural balances such as falling risk. Fall can lead to various kinds of injuries, physical and psychological damage. To overcome and prevent any balance disorders is attempted administration of exercises, one of which is a balance exercise. Balance excercise is very effective for improving functional and static balance and mobility of the elderly. This balance exercise will also reduce the frequency of falls in the elderly, if done with an optimal frequency 3 times a week for 3 weeks it can significantly improve postural stability. To know that balance excercise can reduce the falling risk in elderly. The design of this study used one group pretest-posttest design with population of the elderly in the Eldery Social Center of Mandalika (BSLU) in West Nusa Tenggara. The method using simple random sampling, data collection using Berg Balance Scale dan tested using the wilcoxon test. Result: Before doing balance exercise most of the respondents were included in the risk of Moderate fall is about 31 people (75.61%). After doing balance exercise most of the respondents were at the risk of Moderate fall is about 35 people (85.37%). The result of study was obtained (ρ=0,000). There is an effect of balance exercise on reducing the falling risk in the eldery at Eldery Social Center of Mandalika (BSLU) in West Nusa Tenggara. Nurses are expected to be able to teach the eldery about balance exercise theraphy in order to reduce the falling risk.